2019
DOI: 10.1158/1541-7786.mcr-19-0380
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 Collaborates with ELK3 to Repress E-Cadherin Expression in Triple-Negative Breast Cancer Cells

Abstract: ZEB1 has intrinsic oncogenic functions that control the epithelial-to-mesenchymal transition (EMT) of cancer cells, impacting tumorigenesis from its earliest stages. By integrating microenvironment signals and being implicated in feedback regulatory loops, ZEB1 appears to be a central switch that determines EMT and metastasis of cancer cells. Here, we found that ZEB1 collaborates with ELK3, a ternary complex factor belonging to the ETS family, to repress E-cadherin expression. ZEB1 functions as a transcription… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Unlike MDA-MB231 cells, TGFβ-treated MCF7 cells that display morphological changes of EMT do not show suppression of E-cadherin, a typical epithelial phenotype marker (14). Recently, we reported that ELK3 is highly expressed in TNBC-like MDA-MB231 cells, where it functions as a transcriptional repressor of E-cadherin by collaborating with ZEB1 (15). Therefore, we hypothesized that ELK3 is the missing link that explains the different molecular responses of MDA-MB231 and MCF7 cells when they are treated with TGFβ.…”
Section: Resultsmentioning
confidence: 96%
“…Unlike MDA-MB231 cells, TGFβ-treated MCF7 cells that display morphological changes of EMT do not show suppression of E-cadherin, a typical epithelial phenotype marker (14). Recently, we reported that ELK3 is highly expressed in TNBC-like MDA-MB231 cells, where it functions as a transcriptional repressor of E-cadherin by collaborating with ZEB1 (15). Therefore, we hypothesized that ELK3 is the missing link that explains the different molecular responses of MDA-MB231 and MCF7 cells when they are treated with TGFβ.…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, ZEB1 downregulation mediated by PKCα leads to inhibition of mesenchymal phenotype, cell migration, and invasiveness [ 107 ]. ZEB1 is known to cooperate with ELK3, a ternary complex factor from the ETS TFs family, to repress E-cadherin by transcriptional activation of ELK3 expression [ 108 ]. Suppression of ELK3 through epigenetic activation of GATA3 rendered cancer cells unresponsive to TGF-β and led to their reprogramming into a non-invasive, cuboidal-like, epithelial state, as observed both in vitro and in vivo [ 109 ].…”
Section: Mechanisms Regulating Epithelial–mesenchymal Plasticitymentioning
confidence: 99%
“…Studying the effect of BCL11A zinc protein family members on repressing E-cadherin levels like zinc finger Ebox-binding (ZEB) proteins will be investigated in this study. E-cadherin is a membrane adhesion protein that plays a crucial role in cancer progression and may be repressed by some zinc finger protein family members that encode cysteine two and histidine two (C2H2) gene [24]. E-cadherin is responsible for cell-to-cell adhesion between epithelial cells, resulting in cell layering as well as regulating cell morphogenesis, repression of E-cadherin, and restraining its functions cause the cell-to-cell adhesion and cell integrity to fade gradually [25].…”
Section: Zincmentioning
confidence: 99%